2018
DOI: 10.1016/j.appet.2017.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Domestic food practices: A study of food management behaviors and the role of food preparation planning in reducing waste

Abstract: Recent research has started to show the key role of daily food provision practices in affecting household food waste. Building on and extending these previous contributions, the objective of this paper is to investigate how individuals' everyday practices regarding food (e.g., shopping, cooking, eating, etc.) lead to food waste, and how policy makers and the food industry can implement effective strategies to influence such practices and ultimately help consumers reduce food waste. The research performs three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 53 publications
7
163
0
6
Order By: Relevance
“…One in five Polish respondents "frequently" and "sometimes" throws away cooked starch products or cooked vegetables, and one in three declares that they generally do not use such leftovers to prepare other meals. According to Romani et al [13], as the ability to plan meals increases, the ability to plan purchases improves and overstocking and leftovers are reduced. Stancu et al [22] noted that, even in the absence of planning shopping and meals, the appropriate use of leftovers can contribute to reducing food waste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One in five Polish respondents "frequently" and "sometimes" throws away cooked starch products or cooked vegetables, and one in three declares that they generally do not use such leftovers to prepare other meals. According to Romani et al [13], as the ability to plan meals increases, the ability to plan purchases improves and overstocking and leftovers are reduced. Stancu et al [22] noted that, even in the absence of planning shopping and meals, the appropriate use of leftovers can contribute to reducing food waste.…”
Section: Discussionmentioning
confidence: 99%
“…These were related to such things as checking cabinets/refrigerator before shopping, preparing a shopping list, purchasing unplanned products, shopping in bulk, and purchasing products with a very short expiry date, preparing meals at home, handling food at home, the method of serving meals, using elements of previously served meals in other meals. These topics were selected on the basis of the literature [13,18,23], which shows that these aspects affect food waste in households.…”
Section: Questionnairementioning
confidence: 99%
“…For instance, many households inadequately plan meals (with regard to food provisioning) and grocery shopping (BIO Intelligence Service 2011;WRAP 2011;BCFN 2012;Romani et al 2018). This poor planning can lead to the over-purchase, over-preparation, and over-serving of food (Munro and Marshall 1995;Pearson et al 2013;WRAP 2014;Porpino 2016).…”
Section: Behavioural Determinants Of Household Food Waste Generationmentioning
confidence: 99%
“…All of these predictors were significant antecedents of perceived behavioural control in our study (Table 5). Visschers et al (2016) suggest that food waste reduction interventions should concentrate on intention, perceived behavioural control, and the good provider identity, whereas Stefan et al (2013) and Romani et al (2018) recommend they be built around consumer food planning and shopping routines, while also attempting to integrate a change in consumer attitudes. Our findings generally concur, although we suggest that perceived behavioural control could potentially be exchanged with intention as the key TPB determinant of behaviour, and that intervention development focus on strengthening its significant antecedents.…”
Section: Food Waste Predictors In Other Studiesmentioning
confidence: 99%
“…Other research has shown significant effects on educational interventions by assessing other contexts such as food security (Diplock et al, ; Young et al, ), food waste (Romani, Grappi, Bagozzi, & Barone, ; Stöckli, Niklaus, & Dorn, ) and environmental behavior (Zelezny, ). Still, these researchers suggest that further research on educational intervention is needed.…”
Section: Discussionmentioning
confidence: 99%